THE EFFECT OF WORKING CAPITAL CREDIT FINANCING OF REGIONAL GOVERNMENT BANKS ON THE VALUE OF THE SRI- KEHATI INDEX IN THE CONTEXT OF SUSTAINABLE FINANCE IN INDONESIA - Ruray, Irvan Salafuddin; Pratama, Aditya (Universitas Mercu Buana, 2025)
Abstract – This study analyzes the impact of Working Capital Credit (KMK) financing by RegionalDevelopment Banks (BPD) on the SRI-Kehati Index, which reflects the sustainability performance ofindustrial sectors in Indonesia. Greenhouse gas emissions generated by industrial activities financedby KMK from BPD contribute to the climate change occurring in Indonesia. The study uses secondarydata, including documents, reports, and publications related to BPD financing in the industrial sector.The Vector Error Correction Model (VECM) method is employed to examine the long-term and short-term relationships between KMK financing in five key sectors—agriculture, mining, manufacturing,energy, and construction—and sustainability performance as measured by the SRI-Kehati Index. Theresults indicate that KMK financing by BPD contributes positively to sustainable development in theindustrial sector. The dependent variable used is the SRI-Kehati Index, which measures the social andenvironmental performance of companies, while the independent variables include the agriculture,mining, manufacturing, energy, and construction sectors. KMK financing by BPD can enhancecorporate sustainability performance by prioritizing sustainable business practices and recognizingcompanies that meet certain sustainability standards. Additionally, this financing encourages theadoption of environmentally friendly technologies and responsible business practices. Thus, KMKfinancing by BPD not only plays a role in economic growth but also contributes to climate changemitigation and environmental conservation.Keywords: Regional Development Bank, Bank Financing, Sustainability Performance, SRI-KEHATI